Drivers e barreiras à inovação sustentável na construção civil: evidências do Brasil - Moura, Pedro Henrique Martins (Universidade Federal de São Carlos, 2021)
The intensification of competition between companies has made innovation a fundamental competitive strategy for companies. At the same time, irreversible climate change, environmental pollution, and resource scarcity have made sustainable innovation an important concern in society and an additional competitive factor for companies in general. In this scenario, given the negative environmental impacts caused by the civil construction sector, and aiming at its minimization, sustainable buildings (green buildings) emerged. Although this constructive model has been used worldwide for some time, the understanding of the factors that motivate (drivers) or hinder (barriers) its wide adoption is not yet consolidated. The current literature on the subject presents two important findings: (1) few studies on the subject were developed with a focus on developing countries, such as Brazil; and (2) the existence of contextual variation (country and region) in the factors that motivate or hinder the adoption of this type of innovation. Given this context, the objective of this study was to identify the drivers and barriers to sustainable construction in Brazil. To this end, two systematic literature reviews (RSL) were carried out to build the theoretical model, which supported the study of multiple cases in Brazilian companies in the civil construction sector. There were seven cases selected among construction companies, suppliers, and the certifying body, representing three groups of stakeholders in this sector. As a result, six main drivers were identified that lead organizations active in the sector to implement sustainable construction (certified or not) and seven barriers that hinder such adoption, arising from both internal and external factors to the construction companies. Externally, the main drivers identified were related to consumers (clients' awareness of sustainable buildings, economic benefits offered to clients, and the existence of market demand), and the main barriers identified were related to the government (speaks of government policies and regulations and lack of financial resources and incentives), the local community (resistance to the shift to sustainable buildings) and suppliers (lack of manufacturers and suppliers of sustainable materials). Internally, the main drivers were increased economic benefits for the organization, improved image, and reputation, as well as increased competitive advantage and effective project planning and control. While the main barriers are related to the difficulty in obtaining certifications and the high initial investment of this type of project. Finally, it is concluded that the results point out the drivers and barriers to sustainable construction in Brazil and confront several points of the researched theory. This work contributes to the dissemination of knowledge about sustainable construction since greater knowledge about the drivers and barriers to sustainable construction in Brazil can facilitate the process of adopting sustainable projects and arouse greater interest in investments.
Drivers and barriers to sustainable innovation in civil construction: evidence from Brazil
Keywords: Inovação sustentável; Construção sustentável; Sustainable innovation; Sustainable construction; Green building; Drivers; Barriers; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO